PEMBIAYAAN BUDGET DEFISIT, HUTANG, DAN TINGKAT BUNGA : SUATU PERBANDINGAN ANTARA EMERGING DAN ADVANCED COUNTRIES - Chandra Utama (Bina Ekonomi, 2013)
Deficit budget, public debt, as well as interest rate of advanced and emerging countries are compared in this study. The study employ data of 30 developed countries and 29 emerging countries in period 2006 to 2011. Data is obtained from IMF. The descriptive method is used dominantly in the study. The study finds that the advanced countries conduct more dominant fiscal policy than the emerging countries.  Furthermore, the ratio of public debt per GDP of developed countries also greater than the public debt of emerging countries. However, the percentage of interest payment in the government budget and in the GDP of emerging countries is higher than the developed countries. The situation existed because the interest rates that must be paid by emerging countries are greater than developed countries. If developed countries conduct public debt that requires same ratio of interest payment like emerging countries, the developed countries will have the public debt three times more than the debt of emerging countries. Based on the result, it can be concluded that emerging countries have weaker ability using public debt financing fiscal budget deficit than the advanced countries.